Intertone latency difference of auditory brainstem reflex in patient with endolymphatic hydrops - Ser, Heng Pek (2017)
Intertone latency difference of auditory brainstem response in patient with endolymphatic hydrops Heng Pek Ser1, Nik Adilah Nik Othman1, Mohd Normani Zakaria2, Rosdan Salim1 1 Department of Otorhinolaryngology-Head & Neck Surgery, School of Medical Sciences, Universiti Sains Malaysia Health Campus, 16150 Kubang Kerian, Kelantan, Malaysia. 2 Programme of Audiology and Speech pathology, School of Health Sciences, Universiti Sains Malaysia Health Campus, 16150 Kubang Kerian, Kelantan, Malaysia. Introduction: Idiophatic Endolymphatic hydrops (EH) also known as Meniere’s disease (MD), is a rare disorder of the vestibular system due to abnormal fluctuations in the endolymph fluid causing spontaneous vertigo, fluctuating sensory neural hearing loss (SNHL) associated with tinnitus and aural fullness. Auditory brainstem response (ABR) is a neurologic test of auditory brainstem function in response to auditory stimuli. The intertone latency difference (ITLD) of wave V can be used to measure the transit time of sound from high frequency to low frequency. It has been reported that in EH the transit time is shortened due to increase in basilar membrane stiffness and therefore ITLD can be used clinically to determine EH. Objectives: 1. To establish ITLD as a clinical diagnostic tool for EH. 2. To determine the mean of ITLD in patients with EH. 3. To determine the correlation between ITLD and electrocochleography (ECoG) in EH. Methodology: It was a cross-sectional study by selecting patients with EH based on clinical symptoms and pure tone audiometry (PTA) results. Fourteen patients tested for ITLD and ECoG.The travelling time of wave V at frequency 500 Hz and 4 kHz were calculated. The summation potential and action potential ratio (SP/AP) were measured. Results: Based on Mann-Whitney test, it shown two median of ITLD is not significant for mild and moderate hearing loss (HL), right ear p-value = 0.699, left ear p-value = 0.272. Based on Spearman’s Correlation test, there is a not significant correlation between SP/AP ratio and ITLD (right ear p-value= 0.54, left ear p-value= 0.794) among the participants. Conclusion: Since there was no correlation between ITLD and ECoG. ITLD is important assisting to identify EH, however it might not be useful as a diagnostic tool.